Barriers to digital health services among people living in areas of socioeconomic disadvantage: Research from hospital diabetes and antenatal clinics. (19th September 2021) - Freeman, Toby; Fisher, Matthew; Foley, Kristen; Boyd, Mark A.; Ward, Paul R.; McMichael, Gai; Zimmermann, Anthony; Dekker, Gustaaf
Abstract: Issue addressed: We sought to examine barriers to access to, use of, and benefits from digital health services in an area of socioeconomic disadvantage of Adelaide, Australia. Methods: We conducted waiting room surveys in two hospital diabetes clinics and one hospital antenatal clinic in South Australia, and follow‐up telephone interviews with 20 patients. We examined the extent of access to, use of and benefits from digital health services, and what barriers people encountered. We undertook mixed methods, with quantitative descriptive analysis and qualitative analysis. Results: Thirty‐seven diabetes clinic patients (54% response rate) and 99 antenatal clinic patients (33% response rate) participated. Sixty‐two percent of the patients with diabetes and 27% of antenatal clinic patients had never used digital health services. Seventeen percent of patients with diabetes and 30% of antenatal clinic patients were hesitant users, and 22% of patients with diabetes and 44% of antenatal clinic patients were confident users. Barriers included struggling to afford the technology or to stay connected and a lack of trust in online health information. Potential benefits included feeling more empowered and complementing face‐to‐face care. Conclusions: There are socioeconomic barriers to access, use of, and ability to benefit from digital health strategies that mean not everyone will be able to benefit from digital health services. So What?: As COVID‐19 accelerates the shift towards digital health services, people experiencing socioeconomic disadvantage may be excluded. If barriers to access and use are not addressed, they will exacerbate already increasing health inequities.